Respostas
respondido por:
1
Método da Adição:
x + 2y = 27 (I)
x - 2y = 3 (+) (II)
2x = 30
x = 30/2
x = 15
Substituir em I (x = 15):
x + 2y = 27
15 + 2y = 27
2y = 27 - 15
2y = 12
y = 12/2
y = 6
x + 2y = 27 (I)
x - 2y = 3 (+) (II)
2x = 30
x = 30/2
x = 15
Substituir em I (x = 15):
x + 2y = 27
15 + 2y = 27
2y = 27 - 15
2y = 12
y = 12/2
y = 6
respondido por:
3
x+2 y = 27 | (equation 1)
x-2 y = 3 | (equation 2)
Somar
2X=30
X=30/2
X=15
Substituir
15+2y=27
2y=27-15
2y=12
y=12/2
y=6
x-2 y = 3 | (equation 2)
Somar
2X=30
X=30/2
X=15
Substituir
15+2y=27
2y=27-15
2y=12
y=12/2
y=6
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás